(untitled) (Baghdad Science Journal, 2022)
This work aims to detect the associations of C-peptide and the homeostasis model assessment of beta-cells function (HOMA2-B%) with inflammatory biomarkers in pregnant-women in comparison with non-pregnant women. Sera of 28 normal pregnant women at late pregnancy versus 27 matched age non-pregnant women (control), were used to estimate C-peptide, triiodothyronine (T3), and thyroxin (T4) by Enzyme-linked-immunosorbent assay (ELISA), fasting blood sugar (FBS) by automatic analyzer Biolis 24i, hematology-tests by hematology analyzer and the calculation of HOMA2-B% and homeostasis model assessment of insulin sensitivity (HOMA2-S%) by using C-peptide values instead of insulin. The comparisons, correlations, regression analysis tests were performed by the software of statistical package for the social sciences (SPSS). In pregnant women group, HOMA2-B%, T3, T4, white blood cell (WBC), MID cells, granulocytes (GRAN) increased significantly (p-values˂0.05), while C-peptide level raised about 11% compared to control. Lymphocytes, red blood cells (RBC), platelets (PLT) and hemoglobin (HGB) decreased significantly (p-values˂0.05). Lymphocytes predicted both HOMA2-B% and C-peptide level during pregnancy (R2 =0.516, p ˂0.0004; R2=0.31, p ˂0.009 respectively). Prediction of HOMA2-B% and C-peptide levels by lymphocytes account clarifies that the adaptation in beta-cells might be a part of the defense system mechanism of the body against oxidative stress, and this highlights new insight on the proliferation of beta-cells during pregnancy and insulin sensitivity.